Response to comment on “global diversity and geography of soil fungi” - Tedersoo, Leho; Bahram, Mohammad; Põlme, Sergei; Anslan, Sten; Riit, Taavi; Kõljalg, Urmas; Nilsson, R. Henrik; Hildebrand, Falk; Abarenkov, Kessy (Science, 2015)
Schadt and Rosling (Technical Comment, 26 June 2015, p. 1438) argue that primer-template mismatches neglected the fungal class Archaeorhizomycetes in a global soil survey. Amplicon-based metabarcoding of nine barcode-primer pair combinations and polymerase chain reaction (PCR)-free shotgun metagenomics revealed that barcode and primer choice and PCR bias drive the diversity and composition of microorganisms in general, but the Archaeorhizomycetes were little affected in the global study. We urge that careful choice of DNA markers and primers is essential for ecological studies using high-throughput sequencing for identification.